Strategi Membangun Sinergi Sekolah Dengan Masyarakat Dalam Pengimplementasian Kurikulum Merdeka Belajar Dan Mewujudkan Sekolah Penggerak - Moh. Hanif (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
The implementation of the independent learning curriculum and the driving school program as a new curriculum and program in the education system often becomes a problem for some schools or madrassas, school principals, teachers, students and people outside the school. The most basic problems are more influenced by the provision and application of technology (digitalization of education) as well as demands for superior human resources. This research using a library research approach obtained the following findings; 1) Schools in implementing the independent learning curriculum and efforts to transform into driving schools require synergy with other parties who have direct or indirect interests in the school; 2) Synergy between schools and related parties will be effective if it is positioned as an equal partnership and based on contributions between each party as a mutual exchange of mutual needs or mutual benefits; 3) Schools in building this partnership must have standard concepts and measures as well as rational benefits related to the contribution that the school expects from partners and rational benefits from the school to partners so that strong and harmonious ties are created between schools and partners in implementing the independent learning curriculum and realizing driving school as a shared interest and responsibility.